Experiences of Middle Managers in Transitioning to and Managing Teams in Hybrid Work: An Interpretative Phenomenological Analysis - Teng-Calleja, Mendiola (Archīum Ateneo, 2024)
Purpose The purpose of the study is to explore the experiences and sense-making of middle managers in transitioning to and implementing hybrid work arrangements. Design/methodology/approach Using the lens and analytical procedures of interpretative phenomenological analysis, data were collected during the transition time at the tail end of the COVID-19 pandemic as manyorganizations were navigating the hybrid work setup. In-depth semi-structured interviews were conducted with 12 middle managers from various organizations in the Philippines that have been implementing a hybrid work arrangement for at least 3 months. Findings Findings illustrate the challenges experienced by the middle managers in facilitating a smooth transition to onsite work, managing adjustments on when and where to work and bridging the imperatives of top management as well as the preferences of team members (managing upward and downward). The results describe strategies used by middle managersto balancedeliverablesand employeeneedswhiledemonstrating compassionate leadership in relating with direct reports. The middle managers also engaged in self-care, used reframing and sought support from family and peers to cope with challenges. Practical implications The findings exemplified how the middle managers experience of transitioning to hybrid work reflect various contextual and cultural nuances. These external realities must be considered in providing support to these groups of employees particularly in developing leadership programs that addresses their social and emotional needs.